Effects of Electoral Violence on Voters’ Participation in Nsukka Local Government, Enugu State, 2015 – 2023 - Ruben, Amara Peace; Innocent-Ihekoromadu, Ugo Charity (University of Nigeria Journal of Political Economy, 2026)
Electoral violence remains a significant challenge in Nigeria, affecting the democratic process and voters’ participation. For instance, during the 2015 elections in Nsukka LGA, widespread allegations of voters’ intimidation and ballot box snatching were reported, leading to the disenfranchisement of many voters. The 2019 elections also saw significant security breaches, with documented cases of clashes between political supporters at various polling units and the destruction of electoral materials. According to reports by the Independent National Electoral Commission (INEC), these disruptions contributed to a sharp decline in voters’ turnout compared to previous elections. According to data from the Independent National Electoral Commission (INEC), voters’ turnout in Enugu State saw a decline of nearly 15% compared to previous elections, largely attributed to security concerns and incidents of violence. These examples underscore the persistent and severe nature of electoral violence in the region, necessitating urgent reforms to safeguard democratic participation. This study investigates the impact of electoral violence on voter participation in Nsukka Local Government Area (LGA) of Enugu State from 2015 to 2023. The paper explores the nature, causes, and consequences of electoral violence and evaluates its influence on voters’ turnout, political engagement, and the credibility of electoral processes in the region. Using a combination of primary and secondary sources, the research underscores the need for comprehensive reforms to enhance electoral security and foster citizen participation in democratic processes.